Increased levels of red cell distribution width is correlated with presence of left atrial stasis in patients with non-valvular atrial fibrillation - Adnan Kaya; Ceyhan Tukkan; Ahmet Taha Alper; Baris Gungor; Kazim Serhan Ozcan; Mustafa Adem Tatlisu; Ahmet Ilker Tekkesin; Fatma Ozpamuk Karadeniz; Gulay Gok; Osman Kayapinar (İstanbul Kuzey Klinikleri, 2017)
INTRODUCTION[|]Red cell distribution width (RDW) and neutrophil to lymphocyte ratio (NLR) have been found to be associated with non-valvular atrial fibrillation (AF) and cardiovascular diseases. However, correlation of these parameters with presence of left atrial (LA) thrombus and/or spontaneous echo contrast (SEC) in patients with non-valvular AF has not been clarified. This study was an investigation of correlation of RDW, NLR, and clinical risk factors with LA thrombus and dense SEC in patients with non-valvular AF in the Turkish population.[¤]METHODS[|]The demographic, laboratory, and echocardiographic properties of 619 non-valvular AF patients who underwent transesophageal echocardiography (TEE) examination before direct current cardioversion (DCCV) or AF ablation treatment were retrospectively investigated. Complete blood count (CBC) and biochemical parameters were studied 6 to 12 hours before TEE examination. Left atrial stasis (LAS) markers were noted as presence of left atrial/left atrial appendage (LA/LAA) thrombus or dense spontaneous echo contrast (DSEC).[¤]RESULTS[|]Total of 325 (52%) patients with LAS were compared with 294 patients (48%) without LAS. In the LAS group, there were 274 (84%) patients with LA/LAA thrombus and 51 (16%) patients with DSEC. LAS (+) group, values for RDW (14.85+-1.48 vs. 13.77+-1.30; p<0.01), NLR (2.38 [1.58], vs. 2.10 [1.35]; p<0.01) and C-reactive protein (0.95 [0.61] vs. 0.88 [0.60] mg/L; p<0.01) were significantly higher than seen in LAS (-) group. In multivariate regression analysis, increased level of RDW, age, male gender, heart failure, duration of AF >6 months, and international normalized ratio <2 were independently correlated with presence of LAS.[¤]DISCUSSION AND CONCLUSION[|]Our study indicated that increased level of RDW is independently correlated with higher risk for development of LAS in patients with non-valvular AF.[¤]